2014
DOI: 10.1007/s12160-014-9595-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Electronic Monitoring Influence Adherence to Medication? Randomized Controlled Trial of Measurement Reactivity

Abstract: BackgroundElectronic monitoring is recommended for accurate measurement of medication adherence but a possible limitation is that it may influence adherence.PurposeTo test the reactive effect of electronic monitoring in a randomized controlled trial.MethodsA total of 226 adults with type 2 diabetes and HbA1c ≥58 mmol/mol were randomized to receiving their main oral glucose lowering medication in electronic containers or standard packaging. The primary outcomes were self-reported adherence measured with the MAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 20 publications
1
71
0
Order By: Relevance
“…A weaker correlation was found between the MARS-5 and the electronic monitoring which is consistent with the results of an earlier study [2]. Finally, the sum score of the CQR did not show a significant association with the results of the electronic monitoring.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A weaker correlation was found between the MARS-5 and the electronic monitoring which is consistent with the results of an earlier study [2]. Finally, the sum score of the CQR did not show a significant association with the results of the electronic monitoring.…”
Section: Discussionsupporting
confidence: 89%
“…The intake behavior is quantified by the use of a medication container of which the cap includes a chip that registers the moment of opening [2]. A patient was considered fully adherent if over a period of 1 week the MEMS ® container was opened once or more in accordance with the prescription.…”
Section: Assessment Of Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…One could expect that EM alone, without feedback, can already improve adherence due to the patients' knowing that they are being monitored. However, this view is contradicted by a recent trial showing that EM alone had no statistically significant increase in adherence when compared to standard packaging [32], supporting the importance of the feedback component.…”
Section: Electronically Monitored Dosing Histories and Feedback To Patimentioning
confidence: 94%
“…However, this specific focus enabled a comprehensive investigation of adherence to a commonly prescribed COPD treatment. It could be argued that participants may have changed their inhaler use as a consequence of study enrolment, however previous examinations of a potential Hawthorne Effect (Williams, Amico, Bova, & Womack, 2013) in adherence studies have shown this not to be the case (Sutton et al, 2014).…”
Section: Discussionmentioning
confidence: 99%